Analysis of rainfall data for drought investigation at Agra U.P. - Shri Kant, Shri Kant; Meshram, Sumeet; Sahu, K C (Recent Research in Science and Technology, 2014)
<!–[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]–> This study presents analysis of droughts at Agra district of Uttar Pradesh India. Drought conditions were assessed for yearly time steps using rainfall data for thirty one years (1970 to 2000) at Agra station. According to the India Meteorological department (IMD) an area/region is considered to be drought if it receives seasonal total rainfall less than 75% of its normal value. The rainfall records of 31 years for Agra were obtained from the India Meteorological Department (IMD). Rainfall data has been subjected to various kind of analysis including seasonal & annual rainfall departures, probability distribution and dry spell analysis etc. For identification of drought years and the extent of deficit of annual rainfall, the annual rainfall departure analysis has been carried out. A year is considered as drought year if the total amount of annual rainfall over an area is deficient by more than 25% of its normal value. From the analysis it is observed that in years 1970,1986,1987,1990 and 2000 as moderate drought & years 1972 & 1979 as a severe drought occurred in Agra district, the chance of occurrence of drought in every 10 years varies from 2 to 2.5. It means that year after every 3 to 4 year is a drought year. <!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–>